Pesquisando Práticas e Táticas em Educação Matemática - Bovo, Audria Alessandra [UNESP]; Gasparotto, Giovana Cristina Ferrari [UNESP]; Rotondo, Margareth Sacramento [UNESP]; Souza, Antonio Carlos Carrera de [UNESP] (My University, 2011)
The present article, which is one study among others, seeks to understand practices and tactics of day-to-day school, spanning and being spanned by three studies in Mathematics education. The diversity of scenes, people and strategies used by actors in everyday school, considered from the theoretical perspectives of Foucault and Deleuze, shed light on the ways Mathematic alphabetization takes place and evidence regarding what is present in the black box of school culture, in a constant problematization about what a school can do. Maps are presented that establish cartographies, revealing smooth and striated territories, on a path created by the research done in those schools, where life is always invented.
Researching practices and tactics in mathematics education
Keywords: Cartographies; Mathematic education; Practices, tactics and strategies; School daily